PENERAPAN DAN EFEKTIFITAS 5S DI PERUSAHAAN RETAIL MAKANAN - Jerik Felani; Waluyo Prasetyo (Universitas Islam Raden Rahmat, Malang, 2019)
PT Naku Freight Indonesia (NFI) is engaged in food retail. The inbound and outbound processes include receiving, storing, replenishing, picking, packing and shipping. This process must prioritize the principles of work effectiveness, efficiency, productivity and work safety. The company has implemented a Quality, Safety, Health, and Environment (QSHE) System. One way to implement the QSHE System is by applying Seiri, Seiton, Seiso, Seiketsu, and Shitsuke (Concise, Neat, Clean, Caring, and Diligent) (5S). The 5S method is applied because frequent work equipment placement is not in place. The application of this method is expected to increase work productivity and effectiveness. The purpose of this study was to determine the percentage of application and effectiveness of the 5S Method at PT NFI. The resulting conclusions were: The percentage of achievement in implementing 5S included the application of seiri (sorting) by 100%, seiton (structuring) by 100%, seiso (cleaning) by 100%, seiketsu (stabilization) by 100%, and shitsuke (habituation) by 75 %. The results of this percentage indicated that there was 1 (one) aspect of 5S that has not been applied as a whole, namely Shitsuke. So it can be concluded that the application of Shitsuke at PT NFI has not yet run optimally. If the measurement of the percentage of 5S application was converted into a predicate (qualitative): the application of seiri (sorting), seiton (structuring), the application of seiso (cleaning), seiketsu (stabilization) was carried out